Case report of Stenotrophomonas maltophilia in corneal ulcer: why is it difficult to treat? - Kusumadewi, Yolanda Pitra; Karina, Stefani Melisa; Setyowati, Reny; Suhardjo; Rizki, Ludhang Pradipta (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2024)
Introduction: Stenotrophomonas maltophilia is an opportunistic bacterium and has rarely been reported as a cause of infection in the cornea. Ocular infection due to Stenotrophomonas maltophilia is an opportunistic infection followed by instability of the ocular surface. Casalita et al. (2020), in their research at Cipto Mangunkusumo Hospital, Jakarta, Indonesia found two cases of infected corneal ulcers due to Stenotrophomonas maltophilia. Case description: A 57-year-old man came to the eye clinic with pain in the left eye and blurred vision. The patient was diagnosed with severe corneal ulcer and regularly came for the treatment. The patient felt that his eye suddenly got worse with visual acuity only to his hand movement. Corneal ulcer swab procedure is performed when the patient firstly visit the clinic. Samples are sent to the microbiology laboratory for culture examination. Culture results obtained were coagulase negative Staphylococcus and Stenotrophomonas maltophilia. Conclusion: Stenotrophomonas maltophilia has several virulence factors, including resistance to various antibiotics, making it difficult to treat.